Reforma al artículo innumerado 15 de la ley reformatoria al título v, libro ii del código orgánico de la niñez y adolescencia, en lo referente al monto máximo de una pensión alimenticia, para las personas alimentantes que tengan un solo hijo y que se encuentran en las escalas más altas de la tabla de pensiones - Sánchez Florin, Liliám Claribel (2017)
The right food with the children from their parents, is a subject that always bring a lot of discussions within the legal field, on the one hand, there is the interest of the child duly guaranteed in the Constitution of the Republic and the Code of Children and Adolescence; and on the other hand, is the right of obligors or forced to pay maintenance. In that sense in our country, the Children's Code states that each year the Ministry of Economic and Social Inclusion MIES, set a table pension to which judges are required to apply. However, the above table that dictates the MIES establishes six levels or different scales and in each sets two variables: for one child and two sons on. Here is a big problem for taxpayers who have excellent income and have one son, who is the subject of this study; and is, from level 3 of the table pension given a great inequity against forced with which I do not agree (for example, imagine a person earns four thousand dollars a month and has one son, the pension that would be required to spend approximately in 1600 dollars). Herein lies the main problem, since that amount of money even worse many public servants or workers after work one month paid a salary and that of the pension as an example. From this point of view I think it should amend the Code of Children and Adolescents for more proportional pensions are established and adjusted to the reality of clearing costs in the case of one child; should also take into account that the law determines that the maintenance obligation applies to both the father and mother, ie does not indicate that it is only one parent is responsible for assume